(untitled) (Journal of the College of Basic Education, 2022)
Field experiments were conducted in one of the agricultural fields near Al Rashidiya area to test the effect of fumigation with 2.5, 5, 7.5 gm of Nerium oleander leaf powder on the biological performance of the white fly, Bemisia tabaci, for 10, 20 and 30 minutes inside the greenhouse. The results indicated that the percentage of death of the different instars increased with the increase in the amount of evaporated powder and the time period for evaporation. In general, the results showed that the larval stage was the most affected stage, followed by the adult, nymph, pupal and egg stages, respectively. The cumulative effect of the same amounts used and time periods was also tested, as it was found that there were significant differences in the mortality rate under a probability level of less than 0.05 for all concentrations used.